2017
DOI: 10.1002/ana.24988
|View full text |Cite
|
Sign up to set email alerts
|

Microbleeds in the Secondary Prevention of Small Subcortical Strokes Trial: Stroke, mortality, and treatment interactions

Abstract: Objectives To characterize cerebral microbleeds (CMBs) in lacunar stroke patients in the SPS3 trial and to assess their relationship with recurrent stroke and death, and response to assigned treatment. Methods SPS3 is a randomized, clinical trial conducted between 2003 and 2011. Patients with recent MRI-documented lacunar infarcts were randomly assigned in a factorial design to target levels of systolic blood pressure (SBP; 130–149 mmHg vs <130 mmHg; open-label) and to antiplatelet treatment (aspirin/clopido… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
39
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 33 publications
5
39
2
Order By: Relevance
“…Nineteen studies of ischemic stroke/TIA patients (n ¼ 7672), 11,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] one memory clinic cohort (n ¼ 333), 40 and five population-based studies (n ¼ 13,864) [48][49][50]52 examined the relation between CMBs presence and risk of ICH and ischemic stroke. In the pooled analyses of patients with ischemic stroke/TIA, CMBs presence (vs. no CMBs) was associated with an increased crude risk of ICH (OR: 3.71; 95% CI: 2.13-6.45, p < 0.0001) (Figure 2(a)) and recurrent ischemic stroke (OR: 1.84; 95% CI: 1.39-2.42, p < 0.0001) ( Figure 3(a)) during follow-up.…”
Section: Cmbs and Risk Of Ich And Ischemic Strokementioning
confidence: 99%
See 1 more Smart Citation
“…Nineteen studies of ischemic stroke/TIA patients (n ¼ 7672), 11,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] one memory clinic cohort (n ¼ 333), 40 and five population-based studies (n ¼ 13,864) [48][49][50]52 examined the relation between CMBs presence and risk of ICH and ischemic stroke. In the pooled analyses of patients with ischemic stroke/TIA, CMBs presence (vs. no CMBs) was associated with an increased crude risk of ICH (OR: 3.71; 95% CI: 2.13-6.45, p < 0.0001) (Figure 2(a)) and recurrent ischemic stroke (OR: 1.84; 95% CI: 1.39-2.42, p < 0.0001) ( Figure 3(a)) during follow-up.…”
Section: Cmbs and Risk Of Ich And Ischemic Strokementioning
confidence: 99%
“…Nine cohorts (n ¼ 4715) provided adjusted estimates for CMBs and the risk of future stroke: five for symptomatic ICH (n ¼ 2274) 23,24,26,33,59 and seven for ischemic stroke (n ¼ 3257). 23,24,29,31,33,36,38 In the pooled analysis of these cohorts that provided adjusted estimates, CMBs presence was independently associated with increased risk of ICH (adj-HR: 3.10; 95% CI: 1.78-5.40, p < 0.0001) ( Figure 2(b)), but the increase in the risk for future ischemic stroke was relatively lower (adj- International Journal of Stroke, 13 5Charidimou et al HR: 2.10; 95% CI: 1.58-2.80, p < 0.0001), with intermediate degree of statistical heterogeneity (Figure 3(b)).…”
Section: Cmbs and Risk Of Ich And Ischemic Strokementioning
confidence: 99%
“…[ 40 41 ] In patients with diabetes, LI is more frequently caused by branch orifice atheromatous disease than hypertensive arteriopathy, the latter of which is the predominant vascular pathology underlying strictly deep/mixed CMB. [ 42 ]…”
Section: Acunar I Nfarctmentioning
confidence: 99%
“…A randomised controlled trial is the most reliable test of overall treatment effects and enables estimation of heterogeneity in the effects of treatment in primary subgroup analyses (informed by previous evidence), as well as in other exploratory subgroup analyses. 14 One randomised trial found no heterogeneity by MRI features in the effects of aspirin and clopidogrel versus aspirin alone on stroke recurrence in 1278 adults after subcortical ischaemic stroke, 15 and two other trials found no heterogeneity by the presence of visible infarction on CT in the effects of aspirin versus control on stroke recurrence in 31 072 adults after acute ischaemic stroke. 16 , 17 Randomised trials have not been done—but are needed—to investigate the effects of antiplatelet therapy after intracerebral haemorrhage according to brain imaging features of intracerebral haemorrhage or cerebral small vessel diseases.…”
Section: Introductionmentioning
confidence: 99%